SARS-CoV-2 evolution enhances endocytic uptake while preserving TMPRSS2-dependent fusion - Magnus, Clara L.; Jaber, Zeliha Hamed; Hiergeist, Andreas; Arnold, Lisa; Marchel, Harriet; Lamprecht, Antonia; Hanses, Frank; Dienemann, Thomas; Schneckenpointner, Roland; Lubnow, Matthias; Müller, Thomas; Lunz, Dirk; et al. (Frontiers in Immunology, 2026)
BackgroundOf the five SARS-CoV-2 variants-of-concern (VOC), Omicron shows increased transmissibility and infectivity, but lower pathogenicity. This drop in virulence was associated with an altered entry of VOC Omicron into airway epithelia by endocytosis instead of direct fusion, increasing virus replication in the upper airways and decreasing spread to the lower respiratory tract.MethodsWe aimed to assess the extent of direct fusion and endocytosis in nine clinical SARS-CoV-2 isolates collected during the SARS-CoV-2 pandemic, comprising wild-type (n=1), Alpha (n=2), Delta (n=1), and Omicron (n=5) strains. Viral entry was investigated in four different human cell lines in the presence of camostat, an inhibitor of TMPRSS2-mediated fusion, and aloxistatin, a cathepsin protease inhibitor blocking viral endocytic entry (0.024-100 µM). Full-length viral genomes were obtained using next generation sequencing.ResultsAlpha and Delta variants predominantly entered Calu-3 and Caco-2 cells through TMPRSS2-dependent membrane fusion, whereas Omicron variants – particularly BE.1.1 and BA.5 – showed a pronounced shift toward endocytosis in A549hACE2+/TMPRSS2+ and HEK293T cells. Endocytic uptake was preferentially utilized by strains carrying Δ69/Δ70 and L452R in combination with F486V.ConclusionsAll Omicron variants retained TMPRSS2-dependent fusion activity, indicating that VOC Omicron broadened rather than shifted its cell tropism. While replication in the upper airways and transmissibility are enhanced, the capacity to infect the lower respiratory tract is preserved, which may pose a risk for immunocompromised individuals. The combination of Δ69/Δ70, L452R, and mutations at position 486 may confer a selective advantage, as this constellation is now prevalent in nearly all circulating SARS-CoV-2 lineages.